2003
DOI: 10.1186/1471-2318-3-4
|View full text |Cite
|
Sign up to set email alerts
|

Validity of a novel computerized cognitive battery for mild cognitive impairment

Abstract: BackgroundThe NeuroTrax Mindstreams computerized cognitive assessment system was designed for widespread clinical and research use in detecting mild cognitive impairment (MCI). However, the capability of Mindstreams tests to discriminate elderly with MCI from those who are cognitively healthy has yet to be evaluated. Moreover, the comparability between these tests and traditional neuropsychological tests in detecting MCI has not been examined.MethodsA 2-center study was designed to assess discriminant validity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
275
0
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 278 publications
(281 citation statements)
references
References 38 publications
4
275
0
2
Order By: Relevance
“…The NeuroTrax computerized cognitive assessment battery of tests contains a set of tests designed for early detection of mild cognitive impairment and mild dementia. It also has the capacity to discriminate between cognitively intact individuals with moderate to good correlations demonstrated with the well-validated Wechsler Adult Intelligence Scale battery of tests (11). Good convergent construct validity has been shown between this battery of tests and traditional neuropsychological tests designed to tap similar cognitive domains.…”
Section: Measurement Of Cognitive Functionmentioning
confidence: 94%
“…The NeuroTrax computerized cognitive assessment battery of tests contains a set of tests designed for early detection of mild cognitive impairment and mild dementia. It also has the capacity to discriminate between cognitively intact individuals with moderate to good correlations demonstrated with the well-validated Wechsler Adult Intelligence Scale battery of tests (11). Good convergent construct validity has been shown between this battery of tests and traditional neuropsychological tests designed to tap similar cognitive domains.…”
Section: Measurement Of Cognitive Functionmentioning
confidence: 94%
“…The risk-of-bias criterion for patient selection was high for seven studies, 71,72,[74][75][76]81,83 unclear for one study 86 and low for eight studies. [68][69][70][77][78][79][80]85 The studies were judged to be at high risk for this criterion because a case-control study design was used.…”
Section: Study Quality Assessmentmentioning
confidence: 95%
“…Five studies reported results for more than two groups of participants: three included healthy controls, MCI and early dementia, 71,76,86 and two included healthy controls, early dementia and early dementia/MCI combined. 70,74 In total, 10 studies 68,69,71,72,75,76,78,79,85,86 evaluated the use of automated computerised tests to detect MCI alone, seven studies 70,71,74,76,80,81,86 reported results for early dementia, three studies 70,74,77 reported results for combined MCI/early dementia and one study 83 reported results for human immunodeficiency virus (HIV)-associated neurocognitive disorder (HAND).…”
Section: Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The FTT was developed as part of the Halstead-Reitan Battery (Halstead, 1947) and consists in a test of fine psychomotor performance, measured through self-directed manual motor speed and control (Christianson & Leathem, 2004;Strauss, Sherman, & Spreen, 2006), recurrently employed to assess impairment resulting from traumas, diseases, and other clinical conditions, such as brain injury (Arnold et al, 2005;Hubel, Yund, Herron, & Woods, 2013a;Kane, Roebuck-Spencer, Short, Kabat, & Wilken, 2007), Alzheimer's disease (Arnold et al, 2005;Dwolatzky et al, 2003Dwolatzky et al, , 2004Kane et al, 2007), Parkinson's disease Shimoyama, Ninchoji, & Uemura, 1990), multiple sclerosis Wilken et al, 2003), mild cognitive impairment (Dwolatzky et al, , 2004, and mental retardation (Arnold et al, 2005).…”
Section: Introductionmentioning
confidence: 99%